Nitrogen and Ergosterol Concentrations Varied in Live Jack Pine Phloem Following Inoculations With Fungal Associates of Mountain Pine Beetle - Guevara-Rozo, Sydne; Hussain, Altaf; Cale, Jonathan A.; Klutsch, Jennifer G.; Rajabzadeh, Rahmatollah; Erbilgin, Nadir (Frontiers in Microbiology, 2020)
Bark beetles form symbiotic associations with multiple species of fungi that supplement their metabolic needs. However, the relative contributions of each symbiont to the nutrition of bark beetles have been largely unexplored. Thus, we evaluated the ability of three fungal symbionts of mountain pine beetle to concentrate nitrogen and produce ergosterol while infecting phloem of a novel host jack pine. Ergosterol was used as proxy to determine the fungal biomass (hyphal density) in the current study. We inoculated 80 trees in two forest stands with one of the three fungal species or a non-fungal (control) agar. Six weeks later, we collected phloem from the necrotic lesions induced by the fungi, uninfected tissues adjacent to lesions, and non-inoculated control trees. We found that nutritional contributions varied with fungal species. Nitrogen in lesions was higher in trees inoculated with Ophiostoma montium or control trees, relative to Grosmannia clavigera or Leptographium longiclavatum. Furthermore, concentrations of ergosterol were higher in O. montium lesions compared to other tissues or treatments. These results suggest that O. montium differs from G. clavigera and L. longiclavatum in terms of acquiring nitrogen from host tissues and producing ergosterol.